SUPPLEMENTARY INCOME AND ENHANCING CIVIL SERVANT PERFORMANCE: A Study of The Government of Wajo Regency - Andi Pallawarukka; Armin Arsyad; Diki Diki (Universitas Bina Taruna Gorontalo, 2023)
This study aims to describe and analyze the factors in the implementation of TPP granting policies so that TPP granting in Wajo District does not improve the performance of civil servants. This study uses a qualitative method with a phenomenological study. Data collection was carried out by interviews and literature studies. Data were analyzed by using descriptive analysis and interpretation techniques. The results of the study showed that the factors caused the TPP grant in Wajo District did not improve the performance of civil servants, namely the lack of alignment between the performance targets of civil servants and the performance targets of their superiors and local government; the lack of objectivity in evaluating the performance of civil servants by superiors; the complexity of inputting performance through the e-Kinerja application; Civil servants are more oriented towards fulfilling working hours and tend to ignore performance achievements; Civil servants are not satisfied with the amount of TPP; and the monitoring and evaluation function of the TPP awarding policy has not been optimal. This study suggests that local governments carry out performance management in a more planned and structured manner.